2004
DOI: 10.1046/j.1365-2761.2003.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of in vivo growth on the cellular and extracellular components of the marine bacterial pathogen Photobacterium damsela subsp. piscicida

Abstract: Photobacterium damsela subsp. piscicida, the causative agent of fish pasteurellosis, was grown in vivo. Bacterial cells and extracellular products (ECPs) were analysed via electrophoresis and immunoblot analysis, using specific sea bass antisera. Growth in vivo induced the synthesis of unique bacterial cell proteins at > 206, 206, 21.3, 18, 7.6 and < 7.6 kDa. Sea bass serum raised against live bacterial cells of the pathogen and especially a sea bass serum raised against formalin-inactivated bacterial cells gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
2
12
1
1
Order By: Relevance
“…piscicida recognised antigens of differing molecular weights depending on whether the bacteria had been cultured in vitro or in vivo . The absence of low molecular weight antigens in bacteria cultured in vivo agrees with previous observations [3,4]. Bakopoulos et al [4] identified bands at 52, 44, and 21.3 kDa using sea bass sera raised against live bacteria, and bands at 52, 44, 39.5, 34.7, and 21.3 kDa with sea bass sera raised against formalin inactivated cells cultured in a modified yeast based medium.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…piscicida recognised antigens of differing molecular weights depending on whether the bacteria had been cultured in vitro or in vivo . The absence of low molecular weight antigens in bacteria cultured in vivo agrees with previous observations [3,4]. Bakopoulos et al [4] identified bands at 52, 44, and 21.3 kDa using sea bass sera raised against live bacteria, and bands at 52, 44, 39.5, 34.7, and 21.3 kDa with sea bass sera raised against formalin inactivated cells cultured in a modified yeast based medium.…”
Section: Discussionsupporting
confidence: 87%
“…subsp. piscicida was examined following bacterial growth in dialysis tubing implanted in the peritoneal cavity of sea bass [4]. These authors identified a number of novel antigens associated with the bacterium and ECP, and demonstrated that antigens induced under iron-restriction were conserved on bacteria grown in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the two experiments were that in this study a higher cumulative mortality was achieved, the entire bacterial culture was used as the vaccine without prior isolation of bacterial cells and ECPs, and the challenge was performed with Phdp grown in BHIB 2% NaCl. Despite the fact that the culture medium plays a very important role in the antigens that a pathogen synthesizes and virulence (Bakopoulos et al, 2003a;Bakopoulos et al, 2004), the differences in challenge severity and the modification of the preparation method applied for the experimental vaccine, may account for the contradictory results obtained in this study. Unfortunately, protection of vaccinated sea bass against photobacteriosis under such extreme conditions cannot be compared with previous studies.…”
Section: Discussionmentioning
confidence: 81%
“…d. subsp. piscicida have been identified [1,3,4,21-23,26,28]. The influence of culture conditions on the expression of virulence factors of Ph.…”
Section: Introductionmentioning
confidence: 99%
“…d. subsp. piscicida , which are recognized by the immune responses of fish [1,3-5,26]. In the present study, differences in the antigenicity of the bacterium were examined when the bacterium was cultured in vitro in tryptone soya broth (TSB) or under "near in vivo " conditions in TSB + IR - , GRM, or GRM+ IR - .…”
Section: Introductionmentioning
confidence: 99%